Ditopic N-Heterocyclic pincer carbene complexes containing a perylene backbone - Langbein, Susanne; Wadepohl, Hubert; Gade, Lutz H. (Organometallics, 2016)
A new class of ditopic perylene-based N-heterocyclic pincer ligands, tetrakis(phosphinomethyl)-1,2,3,8,9,10-hexahydrobenzo[1,2,3-gh:4,5,6-g′h′]diperimidine derivatives (TPHDP), were synthesized via a one-pot reaction from 3,4,9,10-tetraaminoperylene either directly with the corresponding phosphine and paraformaldehyde or with the phosphonium salt and triethylamine as base. In this way the diphenyl-, dicyclohexyl-, and isopropylphosphinomethyl-functionalized protioligands were obtained (1a-1c). Reaction of 1a-1c with [RhCl(PPh3)3] led to a double geminal C-H activation and coordination of the ditopic PCP pincer to the rhodium centers, yielding the rhodium(I)chloro complexes (2a-2c) of all three ligands. These were found to be suitable starting materials for further ligand exchange of the chloride. Reaction with lithium phenylacetylide or the abstraction of the chloride ligand with thallium(I) hexafluorophosphate in the presence of neutral donors gave the corresponding alkynyl complexes 3a and 3b or the ionic complexes [Rh(Ph3P)]2-Ph-TPHDP (4a) and [Rh(C5H5N)]2-iPr-TPHDP (4b). The most characteristic feature in the absorption spectra of all compounds is the intense band of the π* ← π transition of the aromatic (perylene) core with its partially resolved vibrational progression. The fluorescence quantum yields (ϕ) of compounds 1a-1c were found to be between 72% and 86%. Upon coordination to rhodium, the intraligand transition in the absorption spectra is only slightly shifted, whereas the fluorescence is almost completely quenched.
Gesehen am 12.06.2020